2016
DOI: 10.1021/acs.chemmater.6b04126
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Treatment as a Detergent of Electronic Trap States in Lead Chalcogenide Nanoparticles

Abstract: Lead chalcogenide (PbX) nanoparticles are promising materials for solar energy conversion. However, the presence of trap states in their electronic gap limits their usability, and developing a universal strategy to remove trap states is a persistent challenge. Using calculations based on density functional theory, we show that hydrogen acts as an amphoteric impurity on PbX nanoparticle surfaces; hydrogen atoms may passivate defects arising from ligand imbalance or off-stoichiometric surface terminations irresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…Constrained DFT Calculations : To assess charge hopping rates ( k CT ) between nanoflakes and reaction intermediates, CDFT calculations were performed, as implemented in the QUANTUM‐ESPRESSO code . The generalized gradient approximation of PBE as the exchange‐correlation functional was used .…”
Section: Methodsmentioning
confidence: 99%
“…Constrained DFT Calculations : To assess charge hopping rates ( k CT ) between nanoflakes and reaction intermediates, CDFT calculations were performed, as implemented in the QUANTUM‐ESPRESSO code . The generalized gradient approximation of PBE as the exchange‐correlation functional was used .…”
Section: Methodsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations have led to an improved understanding of the origin of surface traps in QDs. 14 19 Recently, we have demonstrated that in undoped and charge-balanced nanocrystals only dicoordinated surface chalcogenide atoms should contribute to an electronic state within the band gap for zincblende II–VI nanocrystals. 20 This argument is ultimately based on orbital symmetry and can be expanded to other tetracoordinated (e.g., wurtzite) semiconductor QDs such as the III–V family and invites the prediction that the only requirement to achieve a trap-free QD should be a surface free of dicoordinated anions.…”
Section: Introductionmentioning
confidence: 99%
“…Implementations of CDFT using plane‐wave basis sets appeared more recently, for instance in CPMD, [ 35,36 ] VASP [ 37 ] and CP2K (dual basis). [ 38 ] These plane‐wave implementations enabled CDFT calculations for condensed systems, and facilitated the study of important problems such as redox couples in aqueous solution, [ 35,39 ] charge transfer in biological molecules and proteins, [ 40 ] in quantum dots [ 41 ] and doped nanoparticles, [ 42 ] electron tunneling between defects [ 43 ] and polaron transport [ 44,45 ] in oxides, molecular solids, [ 40 ] and organic photovoltaic polymers [ 46 ] (see References [25] and [2] for extensive reviews). In existing implementations, DFT and CDFT are developed and maintained in the same code, thus requiring direct modifications of core DFT routines to support CDFT functionalities.…”
Section: Introductionmentioning
confidence: 99%